NURSEâS ATTITUDE TOWARD PATIENT SAFETY POLICY IN BALI ROYAL HOSPITAL, INDONESIA: INDIVIDUALIZED APPROACH USING HEALTH BELIEF MODEL - Widya, Dewa Ayu Dyah; Bachtiar, Adang; Ayuningtyas, Dumilah; Permanasari, Vetty Yulianty (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Patient safety is one of the most important dimensions in quality of healthcare. Nurses are the key in care delivery, their compliance toward Patient Safety policy cannot be overlooked. Studies evaluating determinants of nurseâs compliance to Patient Safety policy is still lacking. Aims: To evaluate nurseâs attitude toward Patient Safety policy using Health Belief Model (HBM). Methods: An analytical cross-sectional study was carried on in Bali Royal Hospital, Indonesia, on December 2016. An anonymous, self-administered questionnaire was used to collect the data on socio demographics, knowledge, and attitude toward Patient Safety policy. Attitudes are specifically assessed using HBM. Results: A total of 124 nurses are included in this study. Mean age of the study population was 29.7Â±6.7 years. Mean score for knowledge about Patient Safety policy was 12.68Â±3.40 from 18.0- point scale. Nurses perceived a low risk of non-compliance (mean perceived risk 8.07Â±1.89) and a low barrier to comply with Patient Safety policy (mean perceived barrier 8.66Â±1.78). Knowledge and attitudes toward Patient Safety policy did not differ by sex and educational background but it did differ according to unit of workplace. Age and length of work correlated positively to knowledge (Spearmanâs r=0.439, p-value 0.000; and r=0.400, p-value <0.001, respectively). A positive and moderate correlation was observed between knowledge vs. perceived severity (r= 0.394, p-value <0.001) and knowledge vs. perceived benefit (r=0.422, p-value < 0.001). There was a strong and positive correlation between perceived severity and perceived benefit (r= 0.725, p-value <0.001). Conclusion: Nurseâs attitudes toward Patient Safety policy were generally good and correlate positively with knowledge. The use of HBM provides an increased understanding of how individual perceptions can be influenced to improve nurseâs engagement in promoting safer health care.Â